2018
DOI: 10.1155/2018/1675369
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Diet and Cardiometabolic Risk among Asian Indians in the United States

Abstract: Research studies have shown that plant-based diets confer cardiovascular and metabolic health benefits. Asian Indians (AIs) in the US (who have often followed plant-based diets) have elevated risk for chronic diseases such as diabetes, metabolic syndrome, and obesity suggesting ethnic vulnerability that imply genetic and/or lifestyle causative links. This study explored the association between this ethnic group and diabetes, obesity, and metabolic syndrome after controlling for demographics, acculturation, fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
3
10
0
Order By: Relevance
“…In line with this study, we observed that the vegetarian subjects, despite having lower overall daily calorie intake, recorded a higher per cent energy intake from carbohydrates and lower intake from fats as compared to non-vegetarian subjects and may partly explain the pro-inflammatory state in them. Our results are also supported by recent evidence correlating vegetarian diet with poor health status among Asian Indians in which vegetarianism was found to be associated with higher incidence of metabolic syndrome and obesity (51).…”
Section: Discussionsupporting
confidence: 89%
“…In line with this study, we observed that the vegetarian subjects, despite having lower overall daily calorie intake, recorded a higher per cent energy intake from carbohydrates and lower intake from fats as compared to non-vegetarian subjects and may partly explain the pro-inflammatory state in them. Our results are also supported by recent evidence correlating vegetarian diet with poor health status among Asian Indians in which vegetarianism was found to be associated with higher incidence of metabolic syndrome and obesity (51).…”
Section: Discussionsupporting
confidence: 89%
“…As all patients studied in this paper were residents in the United Kingdom, they were exposed to a similar choice of food types. Whilst our findings suggest that the majority of patients with PD in each ethnic group followed no dietary restrictions, there were dietary differences between the multiethnic PD groups: Asian patients with PD, similar to what has been reported in non-PD populations [17], significantly more frequent followed a vegetarian diet and consumed cumin, turmeric, and cinnamon than White or Black African and Caribbean patients. Both Asian and Black African and Caribbean patients consumed less pork than White patients, and Asian patients consumed less beef and more fresh chili than White or Black African and Caribbean patients.…”
Section: Discussionsupporting
confidence: 84%
“…Unadjusted comparison also suggested higher green tea consumption in Black African and Caribbean patients than in Asian or White patients, but this difference was no longer significant after adjustment for multiple comparisons. Similar differences in diet have been reported in the overall population of Asian and Black African and Caribbean in the United Kingdom [17].…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of diabetes was 17.4%, pre-diabetes 33%, metabolic syndrome 38.2% and obesity 48%. Vegetarianism was not a protective factor for metabolic syndrome and obesity although the risk for diabetes was lowered (9). Paleolithic nutrition, a lowsalt, high-protein diet with virtual elimination of grains and dairy products is thought to reduce the prevalence of metabolic syndrome, but may not be the most suitable diet alteration in India (10).…”
Section: Vegetarianism and Cardio-metabolic Syndromementioning
confidence: 99%